Elements of desirability: exploring meaningful dwelling features from resident’s perspective - Jenni Kuoppa; Niina Nieminen; Sampo Ruoppila; Markus Laine (Taylor & Francis, 2022)
The need for more dweller-oriented approaches to the development of residential environments is widely agreed upon. In the theoretical discussion, the concept of affordances has been seen as promising in grasping the desirable dwelling features and how they become meaningful in everyday uses. However, the concept has been used surprisingly little in empirical housing studies. This article introduces an inventive method to study affordances and contributes to the understanding of the concept by reflecting its usefulness in the context of housing research. The method consists of focus group interviews guided by participant-produced photographs, which allows the participants more freedom to define what they consider meaningful in their dwellings. The results reveal some desirable dwelling features largely uncovered by the public or scholarly discussions yet. From residents’ perspective, developing higher quality housing means paying greater attention to the mundane “secondary spaces”, the sensory experiences and the related atmospheric qualities, as well as the continuums between interior and exterior spaces. The results also emphasize an active role of the resident in discovering and shaping the affordances.